Insect and Hydroponic Farming in Africa : The New Circular Food Economy - Verner, Dorte; Roos, Nanna; Halloran, Afton; Surabian, Glenn; Tebaldi, Edinaldo; Ashwill, Maximillian; Vellani, Saleema; Konishi, Yasuo (Washington, DC: World Bank, 2021)
This book presents a heavily disruptive, inclusive, and resilient solution to Africa’s wide-ranging food security challenges. Specifically, it assesses the benefits and costs of using the frontier agriculture technologies to create a circular food economy in Africa, particularly in Fragility, Conflict, and Violence (FCV)-affected countries. This book focuses on two types of frontier agriculture technologies: insect farming and hydroponic crop farming. Both technologies quickly produce nutritious human food and animal feed and could provide tremendous health, social, economic, climatic, environmental, and food security benefits in Africa. Insect and hydroponic farming can create a circular food economy by reusing society’s organic waste, including agricultural and certain industrial waste, to produce foods for humans, fish, and livestock without the need for vast amounts of arable land or water resources. This book finds that frontier agriculture is a viable complement to conventional agriculture in Africa and could meet many of the continent’s social, economic, environmental, and food security challenges. The book also shows that frontier agriculture can be economically competitive with conventional agriculture in the resource constrained environments of African FCV countries, while generating a fraction of the climate and environmental damage. These frontier agriculture technologies show great potential for growth and scalability as the market is rapidly increasing for novel protein sources from farmed insects and for nutrient-rich fruits and vegetables from hydroponic crops.